Pengaruh Service Quality dan Motif Belanja Hedonik terhadap Kepuasan Pelanggan: Studi Pelanggan Di Antisara Vape Shop Kota Denpasar - I Putu Agus Putra Sasmita; I Made Bayu Dirgantara (Diponegoro Journal of Management, 2025)
Creating a pleasant shopping experience companies can build stronger emotional connections with customers. This study aims to determine the effect of service quality and hedonic shopping motives on customer satisfaction (Customer Study at Antisara Vape Shop Denpasar City). This research used a survey method with a Google Form questionnaire distributed to customers at Antisara Vape Shop in Denpasar City. Data were analyzed using SPSS 26.0 for Windows through descriptive analysis and multiple linier regression. The number of samples used was 120 customers who met the specified criteria.The results showed that service quality has an effect on customer satisfaction. the better the service quality provided by employees, it will increase customer satisfaction. and hedonic shopping motives affect customer satisfaction. the higher the level of hedonic value in the shopping experience, the greater the possibility of increasing the level of customer satisfaction.